Associations of serum neurofilament and asthma: evidence from the NHANES 2013–2014 - Mingming Yang; Xiao Qian; Luqian Zhu; Qiong Xu (Frontiers in Neurology)
BackgroundNeural mechanisms are important in asthma, and serum neurofilament light chain (sNfL) is a biomarker of neuronal damage. This study investigated the correlation between sNfL and asthma.MethodsThis cross-sectional study was based on NHANES data and used multiple logistic regression analysis, subgroup analysis, and smoothed curve fitting to explore the relationship between sNfL and asthma. Covariate selection was validated using the variance inflation factor (VIF).ResultsThe study involved 1773 participants. Results showed that Ln-sNfL (OR = 1.39, 95% CI: 1.03–1.88, p = 0.0325) was positively associated with asthma. Subgroup analyses showed that age, gender, race, education level, marital status, family income, BMI, alcohol use, smoking, diabetes, hypertension and PAMs did not affect the positive association between sNfL and asthma (p > 0.05) (FDR corrected p > 0.1). E-value analysis suggested robustness to unmeasured confounding.ConclusionThere is a positive correlation between sNFL and asthma, and further large-scale and prospective studies are needed to replicate our results and assess the ability of sNfL to predict asthma.